Relevance of depression for anticoagulation management in a routine medical care setting: results from the ThrombEVAL study program. (29th October 2014) - Michal, M.; Prochaska, J. H.; Ullmann, A.; Keller, K.; Gobel, S.; Coldewey, M.; Münzel, T.; Wiltink, J.; Beutel, M. E.; Wild, P. S.
Summary Background Depressive symptoms have detrimental effects on quality of life and mortality. Poor adherence to a treatment regimen is a potential mechanism for the increased risk of adverse medical events associated with depression. Regarding oral anticoagulation with vitamin K antagonists, adherence is crucial for the outcome. Little is known about the clinical relevance of current depressiveness for anticoagulation treatment. Objectives To examine the impact of current depressiveness on anticoagulation treatment in regular medical care. Patients/Methods We examined the association between clinically significant depressiveness as assessed by the Patient Health Questionnaire‐2 ≥ 2 (PHQ‐2 ≥ 2) with the percentage of time in the therapeutic range (TTR), self‐rated compliance, several aspects of health literacy, anticoagulation side‐effects and treatment satisfaction in a cross‐sectional study of 1790 oral anticoagulation outpatients. Results Seven hundred and sixteen participants (40.0%) had clinically significant depressive symptoms. Depressed persons reported lower compliance with intake of prescribed medication and regular visits for control of anticoagulation, more unspecific side‐effects (e.g. pruritus) and lower satisfaction with the anticoagulation treatment and their doctors' expertise and empathy. Depressed as compared with non‐depressed individuals had a lower TTR (−4.67; 95% CI, −8.39 to −0.95). Increasing severity of depressiveness was related with decreasing TTR. However, depressiveness lost its significant impact on TTR after multivariable adjustment (−3.11; 95% CI, −6.88 to 0.66). Conclusions Clinically significant depressiveness was highly prevalent and impaired several aspects of anticoagulation treatment. Depressiveness should be regarded as a clinically significant condition that needs to be addressed in the management of anticoagulation patients.